IMPLEMENTATION OF INKUIRI LEARNING METHOD TOWARDS CHILDREN'S LEARNING CREATIVITY IN RA AL-IKHLAS LABUHAN BATU - Andriani, Rini Dewi; Awaluddin, Awaluddin (Universitas Dharmawangsa Medan, 2021)
Children who were actively doing various activities and carried out well if supported by the right learning methods, in developing creativity the right method was used is the method of playing because by playing children could do creativity according to their desires. As a learning model of many existing learning models, inkuiri was a learning model where in its activities placing teachers as facilitators, teachers guided children as needed.The implementation of this class action research was carried out with two cycles. The first cycle was to increase the development of children's creativity in shake it up through direct guidance in the classroom, and the second cycle was to increase the development of children's creativity in playing shake it up through direct guidance in the classroom or outside the classroom. During the learning process using an inkuiri approach, researchers were assisted by teachers as collaboration partners to observe all activities or activities that occur using observation sheets.From the results of research observations obtained that the learning process of early childhood who use conventional methods (teacher centered), this resulted in low creativity of early childhood (only achieved 22.72% in the initial observation), second: the application of inkuri learning can increase creativity of early childhood. This was shown from the success of children's creativity in the first cycle to 54.54%, and in the second cycle increased to 86.36%.